The influence of the nutrients consumed by health workers during the period of COVID-19 pandemic on hedonic hunger - Arslan, Muge; Edanur Aydin, (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the effects of macro- and micro-nutrient intake of health workers on hedonic hunger. Method: The descriptive, cross-sectional study was conducted at Kahramanmaras Necip Fazl City Hospital, Turkey, from May to December 2021, and comprised all types of healthcare professionals of either gender aged >18 years. Data was collected using a 22-question survey form to record three-day food consumption, and the Power of Food Scale. Data was analysed using SPSS 22. Results: Of the 516 participants, 255(49.4%) were males and 261(50.6%) were females. The overall mean age was 41.28±7.598 years. Body mass indiex was the only factor significantly associated with hedonic hunger (p<0.05), while gender, age, meal-skipping status, the most skipped meal, and the occupational status had no such association (p>0.05). Nurses consumed high-energy macronutrients (p<0.05). Conclusion: Overweight health professionals were found to have the highest rate of hedonic hunger, while nurses’ consumption of high-energy macronutrients was signficantly higher. Key Words: Nutrients, Body mass index, Health personnel, Hunger, Eating.